Examination of Postgraduate Theses on Foam Roller in the Field of Sports Sciences in Turkey - Yusuf Arikan, Mehmet Ilkim, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: In recent years, it is known that myofascial relaxation exercises have become frequently used in the field of sports for both warming up and post-activity relaxation. Foam roller is a widely used tool for the application of self-myofascial release. Foam roller tool is an ideal method that can be applied by the individual himself. In this method, the individual uses body weight to apply pressure to soft tissues during the rolling motion. In this context, many studies have been conducted to examine the self-myofascial release method and the effectiveness of foam roller has been tried to be determined. Aim: The aim of the research is to examine the researches on foam roller in the postgraduate theses published in the field of sports sciences in Turkey. Methods: This research was designed using the systematic review method. Between 01.03.2022 and 02.04.2022, a total of 17 theses were reached as a result of the search made by searching the keywords "foam Rolling, foam roller, köpük silindir" in Turkish-English languages by filtering with the word "Sport" on the database of the National Thesis Center. As a result of the first evaluation made within the framework of the inclusion criteria, it was determined that 5 theses were outside the field of sports sciences and 2 theses were found in the previous scan, and this thesis was not included in the research. Within the scope of inclusion criteria, it was determined that there were 9 postgraduate theses and these theses were included in the research and the data of the research were obtained. Results: It has been determined that the thesis researches on foam roller have been carried out in Turkey since 2018. In addition, it was determined that all theses were at the master's level. In the thesis researches, it was determined that the effectiveness of foam roller applications was compared with various other applications. It has been determined that researches have been carried out especially to increase sportive performance and recovery. Conclusion: It has been concluded that thesis researches on foam roller in the field of sports sciences in Turkey are generally done in order to increase sportive performance and accelerate recovery. In this context, it can be suggested that future studies should be conducted with different sportsmen and larger sample groups.